2020
DOI: 10.1038/s41598-020-58471-z
|View full text |Cite
|
Sign up to set email alerts
|

Detecting coalitions by optimally partitioning signed networks of political collaboration

Abstract: We propose new mathematical programming models for optimal partitioning of a signed graph into cohesive groups. To demonstrate the approach's utility, we apply it to identify coalitions in US Congress since 1979 and examine the impact of polarized coalitions on the effectiveness of passing bills. Our models produce a globally optimal solution to the NP-hard problem of minimizing the total number of intra-group negative and inter-group positive edges. We tackle the intensive computations of dense signed network… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 47 publications
4
44
0
Order By: Relevance
“…Several studies have compared triadic level balance with estimates for the line index of balance, and found that the line index (as a measure of unbalance) correlates with other measures of unbalance, such as the proportion of unbalanced triads 60,61 . Using normalized versions of triadic balance and the line index, high correlation is observed for networks with high density 8,18 , while measurements for sparse networks usually do not match 8 . However, the literature does not clarify whether such correlations are due to similarities in measurement or structural mechanisms in networks that yield similar balance values at different levels.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have compared triadic level balance with estimates for the line index of balance, and found that the line index (as a measure of unbalance) correlates with other measures of unbalance, such as the proportion of unbalanced triads 60,61 . Using normalized versions of triadic balance and the line index, high correlation is observed for networks with high density 8,18 , while measurements for sparse networks usually do not match 8 . However, the literature does not clarify whether such correlations are due to similarities in measurement or structural mechanisms in networks that yield similar balance values at different levels.…”
Section: Resultsmentioning
confidence: 99%
“…These edges can be thought of as sources of tension in this approach. While the historical roots of the frustration index go back to the 1950's 5,50 , this approach only started to receive major attention in recent years 8,9,18,21,51 . This might be due to the computational complexity of obtaining this index exactly, which is an NP-hard problem 52 .…”
Section: Multilevel Evaluation Of Balancementioning
confidence: 99%
See 3 more Smart Citations